PENGGUNAAN MEDIA POWERPOINT DALAM PEMBELAJARAN SENI BUDAYA (MUSIK) DI KELAS VIII SMP N 31 PADANG - Riri Agustin; Yos Sudarman; Irdhan Epria Darma Putra (FBS Universitas Negeri Padang, 2017)
This article aims to determine the improvement of learning outcomes by using the media powerpoint in learning art and culture (music) class VIII in SMP N 31 Padang. The type of research is experimental or experimental research belonging to quantitative research groups in the form of data numbers. Instrument research in the form of pretest, final test (postest), and instrument of observation record. The results of this study indicate that the learning of art and culture (music) in class VIII SMP N 31 Padang done in 4x meeting runs well. It is seen that the use of powerpoint media on music art learning in the class VIII SMP N 31 Padang with the material understand the technique of playing traditional musical instruments in groups. This has a good impact on student learning outcomes in class VIII 3. Improvement of the average score of student learning outcomes before using visual media in the form of powerpoint of 74.53 increased to 88.28 after using visual media in the form of powerpoint. In addition, the visual media in the form of powerpoint can increase the students' curiosity, so as to generate a high sense of enthusiasm and enthusiasm in the learning process, and create an increasingly interesting learning atmosphere that is not boring for students, the media powerpoint can also create a more effective learning process, interactive And efisisen. So that the learning process can run smoothly and can achieve maximum learning objectives. Keywords: Usage, Powerpoint Cultural Art (Music)